DAMPAK SOSIAL DAN EKONOMI INDUSTRI ROKOK TERHADAP KESEJAHTERAAN MASYARAKAT DAN PEREKONOMIAN LOKAL DI KOTA KUDUS - Maulidina, Rista; Kardoyo, Kardoyo (Program Studi Pendidikan Ekonomi Institut Sain dan Kependidikan (ISDIK) Kie Raha Maluku Utara, 2024)
The cigarette industry in Kudus City has a significant impact on the social and economic aspects of the local community. This research aims to analyze how this industry affects the welfare of society and the local economy. Using qualitative methods with a descriptive approach, this research collected data through in-depth interviews, observations and documentation studies related to the cigarette industry in Kudus. The research results show that the cigarette industry plays an important role in creating jobs and increasing regional income, which has a positive impact on the economic welfare of society. However, negative impacts also arise, especially related to public health due to the widespread smoking culture and high economic dependence on this industry. The conclusions of this research emphasize the need to balance economic benefits and social risks through more comprehensive policies to manage social and health impacts.